Study of student perceived effectiveness of the delivery of distance education instruction at the United States Army Command and General Staff College - Weston, Dawn M. (Kansas State University, 2010)
The purpose of this study was to identify current student preferences in order to improve distance education curriculum delivery of the distance education program of the United States Army Command and General Staff College (USACGSC). In this age of rapidly changing contemporary operating environments facing the United States Army, soldiers need up-to-date curriculum in a timely and flexible package with access from remote locations worldwide. This study offered analysis and results from the students’ viewpoints of distance education at the USACGSC. The main research question was: What are student preferences for the delivery of the USACGSC distance education curriculum? To answer this research question, sub-questions needed to be answered. These sub-questions were: (1) What are student preferences for course material delivery? (2) What are student preferences for instructional methods? (3) What are student preferences for collaboration with other students? And (4) What are student preferences for research? The survey data were used to answer the research question and the sub-questions. The data were analyzed using the USACGSC Quality Assurance Office (QAO) standard approved by the USACGSC Deputy Commandant. Based on this study, the researcher recommended making a portion of the USACGSC advanced distributed learning courses face-to-face; making all course material downloadable or issuing course material in print and CD; making coursework self-paced; and making faculty available to all online students.
Keywords: Online Learning; Distance Education; Education, Administration (0514)